Modernity as an Intercultural Network: Uncertainty and new Challenges in a Global Latin America - Calderón, J. Fernando (SocietàMutamentoPolitica, 2018)
The conference speech served as the inauguration event of academic activities in the Centre of Latin American Studies at Cambridge University for the period 2017-2018. The text is a historical and theoretical reflection about the modernity in the region, built in relationship with the different ways of thought that the European illustration had. We, the Latin Americans, are similar but also different. The main idea is that Latin American modernity experiences are Baroque and anti-colonial, as well as intercultural. The analysis places emphasis on a number of social and aesthetic productions and on some sociological experiences.Finally, the text argues that the “historical mirror” the region had with the European modernity projects is broken now and this is associated with the global crisis: “kamanchaka” times, as I named it. For Latin America, the challenge is to re built a new modernity project with a global-horizon perspective.